TEXTURED IN PHOTOSHOP - Henryk, NOGA (Trends in education, 2012)
In the following study techniques of texturing a scene will be presented as well as the way in which one's own textures can be made with the use of photo library. Also, methods of Coping with some basic problem with texturing will be shown and how to successively join various photos in one template. The first thing that must be done before texturing starts is to collect all the referential materials and looking at the variety of surfaces and photos to comprehend a given theme better.
Keywords: new technology; texturing techniques; Photoshop.